Anates: Analysis of Objective Test Item Quality - Ummul Aini; Nurrahmi Lathifa; Mimi Jelita (KIPS Institute, 2025)
The teacher's task is not only to compile and create learning outcomes tests, but the teacher must also pay attention to the quality of the questions that will be given to students, starting from the level of validity, reliability, level of difficulty, distinguishing power, and effectiveness of distracting questions. However, in reality, teachers often only make test questions; teachers forget that the quality of the questions that will be given to students must be known so that they can improve or perfect each question item. The research aims to describe the quality of the multiple choice questions in the odd semester final exam for the class VI Islamic Religious Education and Character Education subject in terms of the validity, reliability, level of difficulty, distinguishing power, and effectiveness of distracting questions. The research method uses descriptive quantitative methods, and the population uses all the answer sheets of class VI students using total sampling techniques. The sample consists of one set of odd semester final exam multiple-choice questions. The data collection technique uses documentation and is processed using the Anates application program version 4.09. The research results showed that of the 20 multiple choice questions, 11 questions had excellent quality, 1 question item had good quality, seven questions had medium quality, and 1 question item had poor quality.